"Reverse Gradualism", Investment Collapse and Monetary Degradation in Russia in the 1990s - Rozmainsky, I.V. (Економічний вісник Донбасу, 2014)
In the 1990s The Russian transitional economy was characterized by many adverse economic processes, but the very important are two of these ones. The first one was the long and biggest fall in output and fixed capital investment. The second was monetary degradation which is increase of primitive mediums of exchange and means of payment – cash, interenterprise arrears ("non-payments") and barter – and (relative and absolute) decrease of "advanced" kinds of money. The goal of this article is to explain interconnections between these processes. The main idea is that these phenomena were generated by shock therapy policy which is turned to be a something like “reverse gradualism”. It means that shock therapy policy is the immediate introduction of all reforms but is not immediate completion of all ones. If that policy takes place, logically later reforms are ended more early because of its extremely small relative duration! That was a case of Russia in the 1990s.